Origin and outcomes the Philippine Competition Act of 2015 (Philippine Law Journal, 2020)
This paper argues that the historical, foreign, and international origins of the Philippine Competition Act of 2015 are highly relevant to achieving the statute's desired outcomes of market efficiency and consumer benefit. They can serve as a useful guide to Philippine courts, competition authorities, and law enforcement agencies for the correct interpretation and effective enforcement of the law. Thus, it is crucial to identify and appreciate the Philippine legal antecedents, model foreign laws, and international law-related policy objectives of the statute.